Cervical Malignant Melanotic Nerve Sheath Tumor with retained PRKAR1A expression and a clinically benign course: a case report and review of the literature - Guranda, Alexandru; Wach, Johannes; Güresir, Erdem; Braune, Max; Kuzman, Peter; Nestler, Ulf (Frontiers in Surgery, 2025)
BackgroundMalignant melanotic nerve sheath tumors (MMNSTs) are rare Schwann cell–derived tumors. Previously classified as benign melanotic schwannomas, they were redefined as a potentially aggressive entity in the 2020 WHO classification of soft tissue tumors and later included in the 2021 WHO CNS classification. However, optimal therapeutic strategies remain under discussion.Case presentationWe present the case of a 46-year-old Caucasian male who underwent surgery for an intra- and extraspinal cervical mass lesion at the C4/5 level on the left side. Immunohistochemical analysis confirmed the diagnosis of MMNSTs. The patient initially presented with ataxia, left-sided weakness, and hemihypesthesia. Magnetic resonance imaging of the cervical spine revealed a left intra- and extraspinal homogeneous contrast-enhancing mass at the C4/C5 level. After the first intraspinal partial resection, the diagnosis of MMNST was established. Gross-total resection is highly recommended in nearly all cases in the literature, followed by adjuvant radiotherapy or chemotherapy in selected cases to prevent metastases, which occur in 15%–42% of cases. The patient postponed the second neurosurgical intervention and declined adjuvant radiotherapy. At 18 months after gross total resection, no recurrent tumor was detected by MRI.ConclusionGiven the limited epidemiological knowledge on MMNSTs, our study contributes to the literature by documenting a case of intra- and extraspinal, cervical MMNST without any of the previously known driver mutations or copy number changes. While the WHO 2021 classification designates these tumors as potentially malignant, our findings support existing reports that more benign courses can occur.